Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 1723530 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Elasmobranchii" ] } The dataset includes 1723530 records from 756 constituent datasets: 11 records from Computarización de la Colección Paleontológica de la Secretaria de Medio Ambiente, Vivienda e Historia Natural, del estado de Chiapas. 28 records from Pelagic fish food web linkages, Queensland, Australia (2003-2005). 166 records from Lizard Island Research Station. 13 records from IIAPPoa. 1 records from Caracterización de la ictiofauna de la ciénaga Honda, Tanguí. 216 records from NORFANZ Biological Survey, Tasman Sea, Australia - New Zealand 2003. 62 records from South Caribbean Diversity. 15 records from Diversité des Poissons de Nouvelle-Calédonie, pêche au filet. 185 records from Rare marine fishes taken in Irish waters from 1786 to 2008. 36 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 302 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 1116 records from CSIRO, fish surveys by the Courageous, 1978-1979. 4 records from Four new species of deep-water catsharks of the genus Parmaturus (Carcharhiniformes: Scyliorhinidae) from New Caledonia, Indonesia and Australia.. 74 records from Códigos de barras de la vida en peces y zooplancton de México. 7072 records from Florida Keys Reef Visual Census 1999. 3 records from OEH Atlas of NSW Wildlife. 15 records from Marine Non Native Species records from Natural Resources Wales (NRW) Monitoring Research and Ad-hoc Sightings. 33 records from imr_mareano_beamtrawl. 907 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 4 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 36 records from National Museum Of Marine Science & Technology. 165 records from Census of the animals of Benin. 210 records from Collection Ichthyologie - SNSD. 62 records from Inventario de algas, corales pétreos, moluscos, crustáceos decápodos, equinodermos y peces de las islas de Revillagigedo, Colima, México. 2 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 2 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 29 records from Marine flora and fauna records from the North-east Atlantic. 5 records from Biodiversidad selecta de los humedales de Laguna de Términos - Pantanos de Centla. 64 records from Suivi des aires marines protégées de Moorea - Peuplements de poissons. 131 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Trawl. 12728 records from Florida Keys Reef Visual Census 2011. 196 records from Seasearch Marine Surveys in the Isle of Man. 23 records from UWBM Invertebrate Paleontology Collection. 1 records from National Taiwan Ocean University. 70 records from Royal Netherlands Institute for Sea Research (NIOZ) - Kom Fyke Mokbaai. 1667 records from Naturalis Biodiversity Center (NL) - Pisces. 194 records from Oregon State Ichthyology Collection. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 2214 records from White shark tagging off New Zealand. 5 records from SUI Vertebrate Collection. 3 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 15 records from Colección de Paleovertebrados del IANIGLA-CCT CONICET Mendoza: IANIGLA-PV. 1 records from ReefWatch. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 23273 records from NMNH Paleobiology Specimen Records. 1951 records from Seasearch Marine Surveys in England. 1 records from Données sur les Poissons de Mayotte (passe en S et passe de Bandrélé). 5 records from Comunidad íctica del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 4601 records from Museum of Comparative Zoology, Harvard University. 204 records from SDSM Vertebrate Paleontology Collection. 2 records from Parmaturus nigripalatum n. sp., a new species of deep-sea catshark (Chondrichthyes: Carcharhiniformes: Scyliorhinidae) from Indonesia. 1 records from Etmopterus lailae sp. nov., a new lanternshark (Squaliformes: Etmopteridae) from the Northwestern Hawaiian Islands. 6 records from Parc_National_de_Port_Cros_2017_12_18. 4 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 1 records from Egg capsules of Atlantoraja cyclophora (Regan, 1903) and A. platana (Günther, 1880) (Pisces, Elasmobranchii, Rajidae).. 7 records from Avistamientos de Biodiversidad Marina / Marine Biodiversity Sightings. 448 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 105 records from MfN Fish Collection, Zoology. 841 records from The Fish Database of Taiwan. 4432 records from observe_tuna_bycatch_ecoscope. 39932 records from University of Florida Vertebrate Paleontology. 1 records from Specimens from India at the University Museum at the University of Bergen. 2984 records from NOAA Pacific Islands Fisheries Science Center, Ecosystem Sciences Division, National Coral Reef Monitoring Program: Stratified random surveys (StRS) of reef fish in the U.S. Pacific Islands. 16 records from A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae).. 10 records from Maculabatis ambigua sp. nov., a new whipray (Myliobatiformes: Dasyatidae) from the Western Indian Ocean. 103 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 3 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 130 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 15 records from Collection des données de biodiversité marine des Iles Eparses (BioReCIE). 469 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Gill Net. 3 records from Freshwater Fishes of Guyana. 21 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 48 records from Marine Offshore Seabed Survey data held by JNCC. 11 records from Diversité des Poissons de Nouvelle-Calédonie, pêche à la roténone. 3 records from Herpetology Collection. 155 records from KUBI Ichthyology Collection. 12802 records from New Zealand research tagging database. 6 records from Acroteriobatus omanensis (Batoidea: Rhinobatidae), a new guitarfish from the Gulf of Oman. 708 records from Natural History Museum Rotterdam (NL) - Chordata collection. 90 records from Fish collection NTNU University Museum. 187 records from Condon Fossil Collection. 80 records from Condition of rocky reef communities around Tasmania: invertebrate surveys, Australia (1992-1995 and 2006-2007). 23 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 8 records from Detección de reclutas de la dorada Sparus aurata como medida del nivel de establecimiento en la Bahía de La Paz, BCS. 984 records from Fish Collection NRM. 51 records from Fish Specimens of Tokushima Prefectural Museum, Japan. 19 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 607 records from Données naturalistes de Philippe KEITH. 4593 records from UF FLMNH Ichthyology. 29 records from Benthos counted on dredged samples during Valdivia cruise VA53. 2 records from Tasmanian Natural Values Atlas. 2597 records from Fish Collection of Hokkaido University. 1163 records from Field Museum of Natural History (Zoology) Fish Collection. 210 records from FSUCML Zoological Collections. 132 records from Macaulay Library Audio and Video Collection. 277 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 4 records from Museu Darder de Banyoles. 5 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 23 records from vertebrate specimens of Kumamoto City Museum. 1 records from Parc_National_des_Calanques_2017_12_18. 1 records from Tejidos colectados en la expedición al municipio Cimitarra, Santander - Proyecto Santander BIO. 3 records from Modernisation 2009-2012 des ZNIEFF de Guyane. 1 records from Peces de agua dulce del municipio de Cimitarra, Santander - Proyecto Santander BIO. 83 records from Artportalen (Swedish Species Observation System). 4 records from Biodiversidad de los recursos marinos y costeros entre Cartagena y el Golfo de Urabá, Caribe colombiano. 430 records from Norwegian Species Observation Service. 6 records from BIOMAERL.Maerl Biodiversity.Functional Structure And Antropogenic Impacts (1996-1998).. 33 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 86 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 35 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Ictiología. 6 records from Données des réserves naturelles nationales gérées par la Ligue pour la protection des oiseaux (LPO). 3936 records from Florida Keys Reef Visual Census 2004. 99 records from Ichthyological Collection of the Museu Oceanográfico D. Carlos I. 140 records from Taiwan Fisheries Research Institute – Digital archives of coastal and offshore specimens. 14 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 157 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 86 records from Environment Agency Rare and Protected Species Records. 150 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 9 records from Urogymnus acanthobothrium sp. nov., a new euryhaline whipray (Myliobatiformes: Dasyatidae) from Australia and Papua New Guinea. 3 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 220 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 6154 records from Florida Keys Reef Visual Census 2014. 264 records from Evaluación estacional de la fauna ictiológica, malacológica y flora ficológica de la Reserva de la Biósfera El Vizcaino, BCS, Fase I: Laguna Ojo de Liebre. 1 records from 2017 North Devon Area of Outstanding Natural Beauty (AONB) Combe Martin Devon Bioblitz. 2 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 1174 records from Natural England Marine Monitoring surveys. 20 records from SPC PROCFish/C Fish Observations Kiribati 2004. 13 records from ISM Ichthyology Collection. 21 records from Ross Sea Biodiversity Survey 2004 (BioRoss). 2075 records from South Australian Museum Australia provider for OZCAM. 11272 records from Soviet Trawl Fishery Data (New Zealand Waters) 1964-1987. 471 records from Seasearch Marine Surveys in Ireland. 23058 records from Rockfish Recruitment and Ecosystem Assessment Survey, Catch Data. 1 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 1 records from MfN - Fossil invertebrates III. 232 records from Diversidad dinámica y patrones reproductivos en la comunidad de peces demersales del Golfo de Tehuantepec. 20515 records from Marine Commercial Fish Survey (FV Kapala, FV Trader Horn, FV Shelley, FV Kirrawa, FV May Bell) in the East and South East Australian Region from 1975 to 2008. 3 records from SIO Benthic Invertebrate Collection. 35 records from Three new stingrays (Myliobatiformes: Dasyatidae) from the Indo – West Pacific. 7 records from Marine Species Records from Skomer Marine Conservation Zone (MCZ) Marine Monitoring Programme. 25 records from DASSH Data Archive Centre volunteer survey data. 134 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Bag Seine. 91 records from Elasmobranquios de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 1164 records from CSIRO, Abundance and distribution of orange roughy in southeast Australian waters 1987-1979. 38 records from HBRG Vertebrates (not Badger) Dataset. 1106 records from NCSM Ichthyology Collection. 44 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 46 records from National Museum of Natural Science. 7 records from Descriptions and revised key to the eggcases of the skates (Rajiformes: Rajidae) and catsharks (Carcharhiniformes: Scyliorhinidae) of the British Isles. 8 records from Galeus corriganae sp. nov., a new species of deepwater catshark (Carcharhiniformes: Pentanchidae) from Papua New Guinea. 1 records from SMNS Palaeontological collection - Invertebrates (Jurassic and Cretaceous). 232 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 13 records from The occurrence status (present/absent) of the fish species associated with the ECOREEF, Discovery Bay, Jamaica (2015-2017). 10 records from Collections ichtyologiques et herpétologiques (BOUM). 27 records from Coastal and Marine Species Database. 10 records from A new wobbegong shark, Orectolobus hutchinsi n. sp. (Orectolobiformes: Orectolobidae) from southwestern Australia.. 184 records from Tasmanian Museum and Art Gallery provider for OZCAM. 1 records from Checklist of the marine and estuarine fishes of New Ireland Province, Papua New Guinea, western Pacific Ocean, with 810 new records. 11 records from Inventario nacional de especies vegetales y animales de uso artesanal. 4 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 9 records from CSUC Vertebrate Collection. 2018 records from KUBI Vertebrate Paleontology Collection. 44 records from UCM Fish Collection (Arctos). 3 records from Seatrust Cetacean Records West Wales. 1 records from Welsh Invertebrate Database (WID). 94 records from Colección Ictiológica de la Universidad Industrial de Santander. 52 records from MBML-Peixes - Coleção de Peixes. 2 records from NE Scotland fish records 1800-2010. 2631 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 3 records from Recursos hidrobiológicos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia BIO. 7204 records from Paleobiology Database. 206 records from Colección Ictiológica del CENPAT-CONICET. 351 records from IndOBIS, Indian Ocean Node of OBIS. 15 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 43 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 63 records from NERP Marine Biodiversity Hub, Theme 1 - Tasman Fracture Commonwealth Marine Reserve Pilot Study - Lobster Potting Component. 79 records from Nova Scotia Museum - Marine Birds, Mammals, and Fishes. 6 records from SPC PROCFish/C Fish Observations Tonga 2008. 74246 records from New Zealand fish and squid distributions from research bottom trawls 1964-2008. 16 records from Biodiversidad íctica de la Isla Cayos de Albuquerque Reserva de Biosfera Seaflower-Proyecto Colombia BIO. 538 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 12 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 83 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 10 records from Isle of Man historical wildlife records 1995 to 1999. 367 records from Australian National Fish Collection Images. 1668 records from VIMS Chesapeake Bay Multispecies Monitoring and Assessment Program. 2 records from flora&fauna(NIBR)2019. 44 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 508 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 2 records from Togo animal redlist. 18 records from Colección de Peces Universidad Católica de Oriente. 331 records from naturgucker. 33 records from Agencement temporel des populations et des peuplements de poissons. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 1 records from Recursos hidrobiológicos de Caño Cristales, La Macarena, Meta. 190 records from CSIRO, Cruise SS199101, Marine Biology Data, Western Australia, 1991. 2 records from BRERC Notable Species records within the last 10 years. 13436 records from iNaturalist Research-grade Observations. 10792 records from Florida Keys Reef Visual Census 2002. 50 records from Ampliación de la base de datos de la ictiofauna insular del Golfo de California. 10494 records from Dry Tortugas Reef Visual Census 2008. 11 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités (Réunion). 356 records from Diversidade e ocorrência de peixes em Inhambane (2009-2017). 2 records from TalTech fossil collections. 223 records from Ictiologia Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 12 records from Données naturalistes de Xavier JAPIOT. 6 records from Données naturalistes de Vincent Prié. 41 records from Abundances of benthic invertebrate species in the CEAMARC region 2007/08. 10498 records from Bureau of Rural Sciences, Commercial Fisheries Presence, Australia, 2000-2002. 8 records from SPC CoFish Fish Observations Niue 2005. 69 records from Série sur le long-terme de Tiahura - Peuplement de poissons. 7 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 20 records from Colección de fauna marina del Centro Oceanográfico de Canarias. 82 records from Juvenile scalloped hammerhead sharks in the Rewa River estuary, Viti Levu, Fiji 2012. 1 records from Mammal collection of National Museum of Nature and Science. 2557 records from Central Great Barrier Reef shark nursery area survey (NERP TE 6.2, JCU), Australia (2011-2014). 53 records from Coleccion de Ictiología del Instituto de Ciencias Naturales (ICN-MHN-Ic). 1 records from Colección Entomológica de Piedras Blancas. 47 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 8 records from Application INPN Espèces: Observations naturalistes, participatives et opportunistes, fondée sur des photographies. 8 records from Collection Pisces - KAUMM. 314 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 11848 records from Florida Keys Reef Visual Census 2008. 1072 records from Fish specimens of Kagoshima University Museum. 1 records from Type Localities for organisms and fossils first described from Antarctica. 27 records from MMNS Ichthyology Collection. 1247 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 25 records from Atlas of Life in the Coastal Wilderness. 123 records from Verified Marine records from Indicia-based surveys. 10 records from Occurrence and distribution of marine wildlife in the Bremer Bay region, Western Australia, Australia (2017). 2 records from Marine Intertidal Phase 1 Species Dataset from the Countryside Council for Wales 1996-2005. 59 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 83 records from Systematic revision of the Potamotrygon scobina Garman, 1913 species-complex (Chondrichthyes: Myliobatiformes: Potamotrygonidae), with the description of three new freshwater stingray species from Brazil and comments on their distribution and biogeography. 5 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 408 records from Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 10 records from SPC PROCFish/C Fish Observations Wallis and Futuna 2005. 2 records from Australian Museum Ichthyology - 2012 Inscription Point. 106 records from AMNH Bird Collection. 43 records from Description of a new species of weasel shark, Hemigaleus australiensis n. sp. (Carcharhiniformes: Hemigaleidae) from Australian waters.. 4 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 47 records from Proyecto peces Río Bita (Puerto Carreño- Vichada) de la Fundación Orinoquía. 2681 records from Reef Life Survey: Global reef fish dataset. 1 records from Freshwater fish records via iRecord. 736 records from Observations issues des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) en 2011 et 2012. 22 records from Two new whiprays, Maculabatis arabica sp. nov. and M. bineeshi sp. nov. (Myliobatiformes: Dasyatidae), from the northern Indian Ocean. 400 records from DFO Maritimes Region Cetacean Sightings. 144 records from SBMNH Vertebrate Zoology. 5 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 6593 records from Florida Keys Reef Visual Census 1997. 1522 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 12 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 1 records from USGS South Florida Fish and Invertebrate Assessment Network Fish. 2 records from CHAS Malacology Collection (Arctos). 66 records from IMOS - AusCPR: Zooplankton Abundance. 120 records from Census of the threatened species of Benin.. 945 records from European Molecular Biology Laboratory Australian Mirror. 36590 records from Programa de Observadores a Bordo (POBCh) de la Secretaria de Pesca de la Provincia del Chubut, Argentina . Observer On board Program -Fisheries Secretariat of the Province of Chubut-Argentina (OOBPPCh). 11906 records from Florida Keys Reef Visual Census 2010. 4282 records from Occurrence records of southern African aquatic biodiversity. 556 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 677201 records from IMOS - Animal Tracking Facility - Acoustic Tracking - Quality Controlled Detections (2007 -2017). 136 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 10 records from Fauna y Flora de Cinaruco - 2014- 2016. 8783 records from NMNH Extant Specimen Records. 438 records from Collection Agnatha fossil SMF. 6 records from Colección de peces de agua dulce del INCIVA. 10 records from Peces asociados a los arrecifes coralinos del norte de Veracruz. 59 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 20 records from SPC CoFish Fish Observations Cook Islands 2007. 7633 records from Northeast Area Monitoring and Assessment Program Near Shore Trawl Survey (NEAMAP). 50 records from Collection d'animaux marins et plantes du Museum d'Histoire Naturelle de Nice. 733 records from Fort Hays State University Sternberg Museum of Natural History - Vertebrate. 1452 records from Museums Victoria provider for OZCAM. 17 records from Fish (ASJK-PI). 409 records from Ichthyology Collection - Royal Ontario Museum. 1 records from CHAS Entomology Collection (Arctos). 6 records from Etmopterus samadiae n. sp., a new lanternshark (Squaliformes: Etmopteridae) from Papua New Guinea. 1153 records from MfN - Fossil Fish Collection. 186 records from Questagame weekly feed. 95 records from Marine biological observation data from coastal and offshore surveys around New Zealand. 111 records from SysTax - Zoological Collections. 4 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Unassessed data. 257 records from UMZC Zoological Specimens. 45 records from Biota occurrence data from plankton surveys around New Zealand. 783 records from Reef Life Survey - Survey Records. 2 records from Etmopterus marshae sp. nov, a new lanternshark (Squaliformes: Etmopteridae) from the Philippine Islands, with a revised key to the Etmopterus lucifer clade. 29 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Bag Seine. 2236 records from Áreas de crianza de tiburones en el Golfo de California. 2 records from Caracterización ecológica y de la diversidad en los ecosistemas de arrecifes de coral y pastos marinos en la jurisdicción marina de CORPAMAG, departamento del Magdalena, Caribe Colombiano. 54 records from Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 2 records from Environnement_Passion_2017_12_18. 4 records from Comunidad íctica de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 22 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 2 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 13 records from MfN - Fossil vertebrates III. 9 records from Bolivian Amazon lowland fish metacommunity data. 1 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 29 records from Porcupine Ray Hunt Data. 25 records from Annotated checklist of the fishes of the archipelago of Madeira (NE Atlantic): I-Chondrichthyes. 19 records from Inventaire des Poissons de la région du Diahot (RAP). 121 records from Paläontologie Marburg. 1 records from Marine invertebrate collection NTNU University Museum. 17 records from Bay of Fundy Species List. 6 records from International Polar Year and Census of Antarctic Marine Life Ross Sea voyage (TAN0802) biodiversity data. 17 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 9 records from Isle of Man historical wildlife records 1990 to 1994. 69 records from UAM Fish Collection (Arctos). 16 records from Megafaunal data from the 2009 BIOFUN trans-Mediterranean deep-sea cruise. 43 records from MSUM Ichthyology and Herpetology Collections. 15 records from Colección de Paleovertebrados del IANIGLA-CCT CONICET Mendoza: IANIGLA-PV. 1513 records from UWFC Ichthyology Collection. 6 records from Argyll Biological Records Dataset. 2 records from SPC PROCFish/C Fish Observations Samoa 2005. 2 records from UF Florida Archaeology Parnell Mound Site (8CO326), Feature 1 Zooarchaeological Data. 8 records from Torpedo formosa sp. nov., a new species of electric ray (Chondrichthyes: Torpediniformes: Torpedinidae) from Taiwan.. 496 records from Collection Pisces SMF. 884 records from Museu Paraense Emílio Goeldi - Paleovertebrate Collection. 154 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Bag Seine. 1 records from Données naturalistes de Benoit FONTAINE. 9898 records from Florida Keys Reef Visual Census 2007. 25 records from SPC PROCFish/C Fish Observations Tuvalu 2004-2005. 1 records from Fauna de Caño Cristales, Sierra de La Macarena, Meta - Colombia. 15526 records from Dry Tortugas Reef Visual Census 2012. 7 records from Collections and observation data National Museum of Natural History Luxembourg. 2 records from Animal Collections Of The Department of Zoology- Nasarawa State University Keffi. 195 records from Lund Museum of Zoology (MZLU). 427 records from Diversité des Poissons de Nouvelle-Calédonie, comptages. 47 records from Epibenthos and demersal fish monitoring at long-term monitoring stations in the Belgian part of the North Sea. 2 records from Diversidad de peces de las lagunas costeras de Pueblo Viejo y el Mango, Veracruz. 1 records from Littlewood Species List. 324 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 259 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 66 records from Fishes of Ghana. 2 records from Fishes of the flooded savannas of Paz de Ariporo, Meta River, Orinoco basin. 23 records from Listado taxonómico de la ictiofauna de la costa de Michoacán. 9000 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 12 records from Electronic Atlas of Ichthyoplankton on the Scotian Shelf of North America (OBIS Canada). 208 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 409 records from Merseyside BioBank (unverified). 7 records from NBIS Records to December 2016. 772 records from Canadian Museum of Nature Fossil Vertebrate Collection. 1 records from BioFokus. 156 records from Naturalis Biodiversity Center (NL) - Museum collection digitized at storage unit level. 19 records from Anymals+plants - Citizen Science Data. 22 records from DASSH Data Archive Centre volunteer sightings records. 29155 records from Investigation of School and Gummy Shark Nursery Areas in South East Tasmania, Australia, 1991-1997. 15 records from Tartu University fossil collections. 711 records from SharkBase. 14 records from Benthos counted on dredged samples during Valdivia cruise VA44. 6 records from Biodiversidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 1334 records from Queensland Museum provider for OZCAM. 33 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 409 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 156 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 135 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 3520 records from Database of the Distributions of Marine Fishes of Arctic Canada. 85 records from Fossil (WSHN-FO). 35 records from Bell Museum fishes. 413 records from Pelagic Fish Observations 1968-1999. 18346 records from International Barcode of Life project (iBOL). 476 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Trawl. 5754 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 41 records from BRERC species records from all years at full resolution excluding Notable Species within the last 10 years. 66 records from Diversité des Poissons de Nouvelle-Calédonie, pêche par chalutage. 42866 records from Fishbase. 16 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 23 records from SPC CoFish Fish Observations Palau 2007. 134 records from Scientific Results of the New Zealand Government Trawling Expedition, 1907. 3 records from Redescription and taxonomic status of Dipturus chilensis (Guichenot, 1848), and description of Dipturus lamillai sp. nov. (Rajiformes: Rajidae), a new species of long-snout skate from the Falkland Islands. 123 records from Données d'occurrences Espèces issues de l'inventaire des ZNIEFF. 2661 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 39 records from UEL - Coleção de Peixes - Museu de Zoologia da Universidade Estadual de Londrina. 133 records from Description of Haploblepharus kistnasamyi, a new catshark (Chondrichthyes: Scyliorhinidae) from South Africa.. 4496 records from Diveboard - Scuba diving citizen science observations. 4 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 30 records from Inventario de la fauna arrecifal asociada al ecosistema de Pocillopora en el Pacífico Tropical Mexicano. 1 records from Artenvielfalt der Nordsee - Helgoland. 152 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 7 records from Actinopterygius Specimens of Akita Prefectural Museum. 63 records from Taxonomic and morphological revision of butterfly rays of the Gymnura micrura (Bloch & Schneider 1801) species complex, with the description of two new species (Myliobatiformes: Gymnuridae). 2831 records from Listado anotado de los tiburones, rayas y quimeras (Chondrichthyes, Elasmobranchii, Holocephali) de México. 5 records from UAFMC Fish. 105 records from ZUEC-PIS - Coleção de Peixes do Museu de Zoologia da UNICAMP. 18 records from Revision of the genus Centrophorus (Squaliformes: Centrophoridae): Part 2 - Description of two new species of Centrophorus and clarification of the status of Centrophorus lusitanicus Barbosa du Bocage & de Brito Capello, 1864. 16 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 129 records from WildNet - Queensland Wildlife Data. 221 records from UAIC Ichthyological Collection. 1 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 25 records from SPC PROCFish/C Fish Observations Fiji 2002-2003. 4181 records from Geographically tagged INSDC sequences. 375 records from Bernice P. Bishop Museum. 2723 records from LACM Vertebrate Collection. 156 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 30 records from COLETA - IMAR/DOP-Uac reference collection from 1977 to 2012. 19 records from Ireland's BioBlitz. 542 records from CUMV Fish Collection. 1 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 283 records from Computarización de la Colección de Referencia para Zoología, Arqueozoología y Paleontología del Museo de Historia Natural de la Universidad Autónoma de Baja California Sur. 375 records from Collections paléontologiques de l'Université Rennes 1. 631 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Trawl. 102 records from Taxonomía y sistemática de la Ictiofauna de la Bahía de Banderas del Estado de Nayarit, México. 414 records from Trawl-survey data in the central-eastern Adriatic Sea (Mediterranean) collected in 1957 and 1958. 8 records from Marine Data from The Wildlife Trusts (TWT) Dive Team; 2014-2018. 10 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ameghino National Collection (MACNA). 891 records from Trawl survey data from the Jabuka Pit area (central-eastern Adriatic Sea, Mediterranean) collected between 1956 and 1971. 210 records from Données BioObs - Base pour l’Inventaire des Observations Subaquatiques de la FFESSM. 15 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 45 records from Biogeography of near-shore reef fishes in northern New Zealand. 146 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 3 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 242 records from Seasearch Marine Surveys in the Channel Islands. 323 records from PPEAO - Pêches scientifiques. Peuplements de poissons des écosystèmes estuariens, lagunaires et continentaux d'Afrique de l'Ouest. 7012 records from Florida Keys Reef Visual Census 2003. 21 records from Ohio State University Fish Division (OSUM). 23 records from SEWBReC Fish (South East Wales). 638 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 37 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 145 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 3506 records from NCSM Vertebrate Paleontology Collection. 7662 records from Chondrichthyans Of Ireland. 34 records from DASSH Data Archive Centre Academic Surveys. 80 records from SPC CoFish Fish Observations Marshall Islands 2007. 1 records from Diet analysis of Pacific Bluefin Tuna larvae. 3 records from Vertebrate collections of the Department of Animal Biology and Conservation Sciences, University of Ghana. 1 records from Colección de Ictiología. 5 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 155 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 602 records from Données naturalistes de Jean-Jacques RIUTORT. 66 records from National Taiwan Museum. 4 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 10 records from Arctic Ocean Diversity. 65802 records from ECNASAP - East Coast North America Strategic Assessment. 7784 records from Dry Tortugas Reef Visual Census 2006. 454 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Bag Seine. 14942 records from Catch data from New Zealand research trawls since 2008. 5 records from Notoraja martinezi sp. nov., a new species of deepwater skate and the first record of the genus Notoraja Ishiyama, 1958 (Rajiformes: Arhynchobatidae) from the eastern Pacific Ocean. 59 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 2 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 30 records from Colección de peces del Museo de Historia Natural de la Pontificia Universidad Javeriana. 1491 records from North Marine Region demersal fish and invertebrate collection records (DEW collation), Australia (1980 - 1997). 330 records from RBINS DaRWIN. 124 records from North Marine Region whaler shark collection records (DEW collation), Australia (1999- 2005). 7561 records from Natural History Museum (London) Collection Specimens. 13 records from Listado ictiofaunístico de las bahías del Parque Nacional Huatulco, Oaxaca, México. 2 records from On the composition of the benthic fauna of the western Fram Strait. 4 records from MCNH Museum of Cultural and Natural History Fish Collection. 18 records from Tejidos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 2010 records from Fishes in the Argentine Sea from 1967 to the present time. 186 records from Queen Victoria Museum Art Gallery provider for OZCAM. 1042 records from Seasearch Marine Surveys in Wales. 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 23 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités. 8 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 472 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 1995 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 1 records from Fishes from Madagascar Reef, Campeche Bank, México. 4114 records from Capture Mark Recapture Data for Scottish Elasmobranchs: 2009-2018. 1 records from Caracterización y monitoreo de la condición arrecifal en cinco áreas naturales protegidas y un área de influencia de Quintana Roo, México: Primera etapa. 18 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Tridens00/5. 59 records from The Australian Zooplankton Database (1938 onwards). 2303 records from Dry Tortugas Reef Visual Census 2000. 4 records from Monitoreo complementarios de algas, invertebrados y peces en el Parque Nacional Arrecifes de Cozumel. 6 records from Fish distribution data, Mayor Is. (Tuhua) marine reserve 1993. 1 records from Aportes al conocimiento de la biodiversidad de aguas profundas del mar Caribe colombiano. 45 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM-IEOMA. 708 records from Waarnemingen.be - Fish occurrences in Flanders and the Brussels Capital Region, Belgium. 6 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 5472 records from Dry Tortugas Reef Visual Census 2016. 3 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 11 records from Himantura hortlei n. sp., a new species of whipray (Myliobatiformes: Dasyatidae) from Irian Jaya, Indonesia.. 503 records from Biological Reference Collections ICM CSIC. 33 records from Epibenthos and demersal fish monitoring in function of dredge disposal monitoring in the Belgian part of the North Sea. 1866 records from Image Database of Fishes in the Kanagawa Prefectural Museum of Natural History. 696 records from Reef Life Survey: Cryptic Fish. 8 records from Checklist of the Red Sea Fishes with delineation of the Gulf of Suez, Gulf of Aqaba, endemism and Lessepsian migrants. 7089 records from School and gummy shark tagging by CSIRO in southern Australia: 1947-1956. 90 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 44 records from Paleontological Research Institution Collections. 14842 records from Dry Tortugas Reef Visual Census 2014. 958 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 35 records from Fish (NHMK-PI). 533 records from Poissons d'eau douce de Guyane française. 52 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 1394 records from The Fish Collection. 98 records from ASEAN Fish Occurrences Literature. 50 records from Evaluación de la ictiofauna en las áreas focales del corredor biológico costero-Yucatán. 13734 records from Florida Keys Reef Visual Census 2012. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 40 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 2 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 33 records from The catshark genus Scyliorhinus (Chondrichthyes: Carcharhiniformes: Scyliorhinidae): taxonomy, morphology and distribution. 6 records from Ichthyologie ZMK. 1 records from NCSM Invertebrate Paleontology Collection. 1121 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Gill Net. 1 records from Ichthyofauna of piedmont and savannah environments in the Casanare River drainage, Orinoco Basin, Colombia. 2314 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 1 records from Fish specimens of Kaizuka City Museum of Natural History. 168 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from POPA- Fisheries Observer Program of the Azores: Accessory species caught in the Azores tuna fishery between 2000 and 2013. 8 records from SPC CoFish Fish Observations Nauru 2005. 31 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 1 records from Fish Collection Ismael Kong, Universidad de Antofagasta, Chile. 36 records from Colección de Peces de la Universidad de Antioquia. 33 records from MVZ Hildebrand Collection (Arctos). 551 records from Vertebrate Paleontology Division, Yale Peabody Museum. 1 records from The Rock Pool Project database - intertidal species records from rocky shore habitats - from February 2019. 2 records from General Biodiversity Records from Ireland. 10 records from ImagDOP Benthic Video Annotations in Condor seamount in 2010. 18 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 9540 records from Florida Keys Reef Visual Census 2006. 495 records from SA Fauna (BDBSA). 646 records from Seasearch Marine Surveys in Scotland. 1203 records from CSIRO, fish surveys by the Soela, 1980s. 1 records from Mammals Specimens. 49 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 680 records from Northern Territory Museum and Art Gallery provider for OZCAM. 934 records from Elasmobranquios mexicanos. 1 records from A new genus and species of catshark (Carcharhiniformes: Scyliorhinidae) from eastern Indonesia. 38 records from Trawl-survey data in the Adriatic Sea (Mediterranean) collected in 1972, 1975 and 1981. 1 records from Peces del Distrito Nacional de Manejo Integrado Cabo Manglares Bajo Mira y Frontera, Pacífico colombiano - Proyecto Colombia BIO. 717 records from Trawl-survey data from the “expedition Hvar” in the Adriatic Sea (Mediterranean) collected in 1948-1949. 248 records from Jervis Bay Marine Ecological Studies (JBMES) 1988-1991. 318 records from CSIRO, Jack Mackerel surveys, 1978. 3 records from Weddell Sea macrozoobenthos EASIZ I. 48 records from DASSH Data Archive Centre - Statutory Surveys. 137 records from IOW Natural History & Archaeological Society Marine Records. 270 records from KUBI Ichthyology Tissue Collection. 8002 records from Florida Keys Reef Visual Census 2005. 16 records from Marine Life Society of South Australia. 5906 records from CSIRO Ichthyology provider for OZCAM. 296 records from Computarización de la Colección Nacional de Peces del Instituto de Biología UNAM. 46 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 131 records from flora & fauna(NIBR). 7 records from A new Eastern Central Atlantic skate Raja parva sp. nov. (Rajoidei: Rajidae) belonging to the Raja miraletus species complex. 397 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 81 records from Fish (JNHM-PI). 136 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Rhinobatos manai sp. nov., a new species of guitarfish (Rhinopristiformes: Rhinobatidae) from New Ireland, Papua New Guinea. 641 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 1 records from Actualización de la Colección Nacional de Peces dulceacuícolas mexicanos, ENCB. 1 records from MSB Host Collection (Arctos). 11 records from Merseyside BioBank Active Naturalists (unverified). 11 records from Etmopterus burgessi sp. nov., a new species of lanternshark (Squaliformes: Etmopteridae) from Taiwan.. 3 records from Palaeobiology collection, FAU Erlangen. 31 records from Underwater fish visual census in the Azores from 1997 to 2015. 48 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 109 records from Projet Diable de mer - AILERONS. 1103 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Gill Net. 179 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 28 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz. 2 records from Fishes of the Cusiana River (Meta River basin, Colombia). 347 records from Sizing Ocean Giants. 3 records from A new species of whiptail stingray of the genus Dasyatis Rafinesque, 1810 from the Southwestern Atlantic Ocean (Chondrichthyes: Myliobatiformes: Dasyatidae).. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 439 records from Palaeozoological Collections (PZ), Swedish Museum of Natural History (NRM). 103 records from The reptiles, amphibians and fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from CHAS Ichthyology Collection (Arctos). 71 records from Gaia Guide. 5 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 4 records from Yorkshire Naturalists Union Marine and Coastal Section Records. 1 records from Fish (NSMK-PI). 338 records from CNPE/Coleccion Nacional de Peces. 7 records from Données d'observation de la mégafaune marine issues des campagnes océanographiques en France métropolitaine. 67 records from Diversité des Poissons de Nouvelle-Calédonie, pêche à la ligne à main. 5846 records from University of California Museum of Paleontology. 6 records from Chondrichthyans Specimens of Akita Prefectural Museum. 8 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 11 records from Natural History Museum, University of Tartu. 41 records from Observations de poissons marins du Fish Watch Forum. 18 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 274 records from Fish Collection of Natural History Museum and Institute, Chiba. 292 records from A dataset from bottom trawl survey around Taiwan. 1 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 6 records from RNF - Données de l'association Vivarmor Nature. 45 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 2 records from Offshore Fish Species in Kingdom of Tonga. 5 records from MfN - Fossil vertebrates IV. 39 records from Fish Collection of Yokosuka City Museum. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 34 records from Urolophus kapalensis sp. nov., a new stingaree (Myliobatiformes: Urolophidae) off eastern Australia.. 153 records from Données naturalistes de Pierre NOEL (stage). 3773 records from FBIP:SAEON: Historical Research Survey Database (1897-1949). 228 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 1381 records from Diversidade e ocorrência de peixes na Zambézia (2003-2016). 17 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 13 records from Colección Hidrobiológica del Chocó. 3369 records from CAS Ichthyology (ICH). 480 records from CM Vertebrate Paleontology Collection. 523 records from Fisheries Research Laboratory, Mie University. 358 records from The Fish Collection at the Zoologische Staatssammlung München. 40842 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 389 records from Fauna Atlas N.T.. 3 records from Inventaire de l'îlot du Lédénez Vraz. 299 records from Monitoring of reef fish abundance in the Tsitsikamma National Park using stereo-BRUVs. 44 records from VMNH SVDM Vertebrate Paleontology. 9 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 1416 records from Western Australian Museum provider for OZCAM. 80 records from Marine Records from Pembrokeshire Marine Species Atlas. 9274 records from Dry Tortugas Reef Visual Census 2004. 19 records from National Trust Species Records. 11 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 15 records from Fish Collections at the South China Sea Repository and Reference Centre, Universiti Malaysia Terengganu, Malaysia. 57 records from Asia-Pacific Dataset. 259 records from Museu Paraense Emílio Goeldi - Ichthyology Collection. 95 records from TPWD HARC Texas Coastal Fisheries, Corpus Christi Bay Gill Net. 1 records from NRW Regional Data: North Wales. 12 records from VMNH SUP Paleontology Vertebrates and Paleobotony. 4 records from LERN Records. 2452 records from SIO Marine Vertebrate Collection. 152 records from Auckland Museum NZ Marine Collection. 2 records from Cybelle Méditerranée. Observation nautique avec effort d'observation. 65 records from Miscellaneous records held on the Cofnod database. 20 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 1703 records from Fish collection of National Museum of Nature and Science. 1 records from UAM Earth Sciences Collection (Arctos). 2 records from iRecord Surveys. 33 records from Dataset of the multidisciplinary research surveys in the seamounts of Ewing and Valdivia Bank (Walvis Ridge) - SE Atlantic. 2 records from A new skate genus Orbiraja (Rajiformes: Rajidae) from the Indo-West Pacific. 2 records from Collection Paleoanthropology SMF. 177 records from Biological observations from the Discovery Investigations 1925-1952. 2 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 107 records from Ibaraki Nature Museum, Fish collection. 111 records from AUM Fish Collection. 3861 records from Australian Museum provider for OZCAM. 1 records from Colección de Referencia de Peces del Museo de Ciencias de la Universidad El Bosque. 1 records from CSIRO, Cruise SS200702, Marine Biodiversity Survey, Southeast Australia, 2007. 6 records from Marine Biological Sample Database, JAMSTEC. 6 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 393 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 1465 records from Observation.org, Nature data from the Netherlands. 312 records from CSIRO, Fish Survey, Albatross Bay - Gulf of Capentaria, North Australia, 1986-1988. 2050 records from Demersais survey in the Azores between 1996 and 2013. 288 records from Ghent University - Zoology Museum - Vertebrate collection. 10 records from Estonian Museum of Natural History. 245 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Bag Seine. 1 records from The extinct river shark Glyphis pagoda from the Miocene of Myanmar and a review of the fossil record of the genus Glyphis (Carcharhiniformes: Carcharhinidae). 315 records from Arctic Species Trend Index (ASTI) : Marine. 5 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 128 records from LSUMZ (LSU MNS) Fishes Collection. 8499 records from Florida Keys Reef Visual Census 2000. 11 records from Redescription of the rare and endangered Broadfin Shark Lamiopsis temminckii (Müller & Henle, 1839) (Carcharhiniformes: Carcharhinidae) from the northeastern Arabian Sea. 16 records from Actualización de la base de datos computarizada de la colección ictiológica de la Universidad Autónoma de Baja California. 30 records from Descriptions of skate egg cases (Chondrichthyes: Rajiformes: Rajoidei) from the eastern North Pacific.. 28 records from Description of Rhinobatos ranongensis sp. nov. (Rhinopristiformes: Rhinobatidae) from the Andaman Sea and Bay of Bengal with a review of its northern Indian Ocean congeners. 39 records from Fish biodiversity in three northern islands of the Seaflower Biosphere Reserve Colombian Caribbean. 6 records from Ecosystem biomonitoring with eDNA: metabarcoding across the tree of life in a tropical marine environment. 840 records from Pacific Ocean Shelf Tracking (OBIS Canada). 15 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleovertebrates National Collection (MACNPv). 13 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 6 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 1 records from A new Western North Atlantic Ocean kitefin shark (Squaliformes: Dalatiidae) from the Gulf of Mexico. 1 records from Röntgenarchiv Wilhelm Stürmer - SMF. 66 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 635 records from Canadian Museum of Nature Fish Collection. 11951 records from Florida Keys Reef Visual Census 2001. 12 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 2 records from Colección de Paleovertebrados. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 1 records from Ictiofauna Asociada a los Cativales del Municipio de Riosucio, como Aspecto Relevante dentro de la Estructura Ecológica Principal del Chocó Biogeográfico. 1 records from Miscellaneous records held by BIS. 12 records from Arctic Marine Fish Museum Specimens. 1 records from Données sur la biodiversité des récifs coralliens de Martinique (OMMM). 378 records from Registros ictiofaunísticos de localidades selectas de 10 regiones marinas prioritarias del Pacífico Mexicano. 2 records from Ictiofauna de la Orinoquia Andina de Colombia. 396 records from Fish specimen database of Osaka Museum of Natural History. 2388 records from CSIRO, Rachel Cruises, Shark Data, Arafura Sea, North Australia, 1984. 11 records from Norwegian Biodiversity Information Centre - Other datasets. 813 records from University of Michigan Museum of Zoology, Division of Fishes. 100 records from DNA metabarcoding assays reveal a diverse prey assemblage for Mobula rays in the Bohol Sea, Philippines. 6 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Pisces (ZUFMS-PIS). 1 records from Redescription of Squalus acutipinnis Regan, 1908, a Valid Species of Spiny Dogfish from Southern Africa (Chondrichthyes: Squaliformes: Squalidae). 1 records from Historical review, catalog of type specimens and online database of the ichthyology collection of the Instituto de Ciencias Naturales of the Universidad Nacional de Colombia (ICN-MHN). 3951 records from Dry Tortugas Reef Visual Census 1999. 3 records from MSB Fish Collection (Arctos). 80 records from Diversité des Poissons de Nouvelle-Calédonie, pêche à la palangre. 1 records from New sighting of the endangered species blackchin guitarfish, Rhinobatos cemiculus, in the South Aegean Sea. 317 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Gill Net. 2 records from Description of the egg cases of Dentiraja polyommata (Rajiformes: Rajidae) and Asymbolus pallidus (Carcharhiniformes: Scyliorhinidae) from Queensland, Australia. 5 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 2 records from Leucoraja elaineae sp. nov., a new rough skate (Rajiformes: Rajidae) from the Western Indian Ocean. 973 records from SEFSC CAGES Alabama Fish Length Data with CPUE. 8 records from Palaeontological collections National Museum of Natural History Luxembourg. 21 records from Colección de Tejidos del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-CT). 27 records from Florida Fish and Wildlife Conservation Commission - Freshwater Fishes of Florida - 1956-2000. 104 records from National Trust for Scotland Species Records. 4 records from Marine Education Society of Australasia. 37 records from SPC PROCFish/C Fish Observations Solomon Islands 2006. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 1 records from Données Nord-Pas-de-Calais. CMNF. 388 records from Fish collection, Natural History Museum, University of Oslo. 23543 records from ecoscope_observation_database. 7 records from Bythaelurus bachi n. sp., a new deep-water catshark (Carcharhiniformes, Scyliorhinidae) from the southwestern Indian Ocean, with a review of Bythaelurus species and a key to their identification. 1 records from Descriptions of some vertebrate remains from the Fort Union beds of Montana. 4 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 54 records from Protected species bycatch in New Zealand fisheries. 2040 records from Florida Keys Reef Visual Census 1994. 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 5 records from NatureServe Network Species Occurrence Data. 4702 records from Florida Keys Reef Visual Census 1995. 205 records from ALA species sightings and OzAtlas. 2093 records from Elasmobranquios del Golfo de Tehuantepec, litoral chiapaneco. 35 records from Zanobatus maculatus, a new species of panray from the Gulf of Guinea, eastern central Atlantic (Elasmobranchii: Batoidea: Zanobatidae). 3 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 574 records from Ocean Genome Legacy Collection. 24 records from WDC Shorewatch Sightings. 11296 records from Dry Tortugas Reef Visual Census 2010. 4200 records from SBC LTER Darwin Core Archive: Kelp Forest Reef Fish Abundance. 3 records from Données naturalistes de Pierre-Yves NOEL. 1 records from Fauna y flora del municipio de Lipa, Arauca. 24 records from Azorean Biodiversity Portal. 16184 records from Florida Keys Reef Visual Census 2009. 3 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1 records from Cybelle Méditerranée. Observation nautique ponctuelle. 48 records from Non-vertebrate Paleontology, Jackson School Museum of Earth History, University of Texas at Austin. 4 records from Marine metagenomes Metagenome. 2 records from A new legskate, Sinobatis andamanensis (Rajiformes: Anacanthobatidae), from the Andaman Sea (northeastern Indian Ocean). 408 records from Fish: Records for Kent.. 514 records from An annotated checklist of the chondrichthyans of Papua New Guinea. 2 records from DASSH Data Archive Centre expert sightings records. 1868 records from Peces batoideos de la plataforma continental del Golfo de Tehuantepec. 2436 records from Florida Keys Reef Visual Census 1996. 512 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Trawl. 19 records from Epibenthos and demersal fish monitoring data in function of wind energy development in the Belgian part of the North Sea. 588 records from Distribution of 15 major fish species in the North Sea between 1959 and 1979. 3 records from Australian Museum Factsheets. 3 records from Données naturalistes de Pierre NOEL (pnoel). 3557 records from Bottom Trawl Surveys: Catch and Effort Data For South East Australia, 1898-1996. 39 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 1 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 9 records from Bythaelurus vivaldii, a new deep-water catshark (Carcharhiniformes, Scyliorhinidae) from the northwestern Indian Ocean off Somalia. 1 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleoinvertebrates National Collection (MACNPi). 12 records from Poissons des mangroves et des zones humides du sud Togo. 51 records from Collection Anatomie Histologie - SMF. 1 records from Ictiofauna Presente en la Ciénaga de Montaño, Municipio del Carmen de Atrato. 7415 records from Florida Keys Reef Visual Census 1998. 605 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 33 records from Taxonomic status of maskrays of the Neotrygon kuhlii species complex (Myliobatoidei: Dasyatidae) with the description of three new species from the Indo-West Pacific. 14 records from Epibenthos and demersal fish monitoring in function of aggregate extraction in the Belgian part of the North Sea. 27 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 4 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 233 records from University of Texas, Biodiversity Center, Ichthyology Collection (TNHCi). 2 records from 1778-1998 Ivor Rees North Wales Marine Fauna Ad-hoc sightings shore and ship-based surveys. 102 records from Condrictios del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 3 records from Censo de biodiversidad marina Edo. Miranda. 4 records from Occurrences in SinBIOTA. 1 records from Florida Museum Environmental Archaeology Baptizing Springs Zooarchaeological Data. 6522 records from Florida Keys Reef Visual Census 2016. 8 records from Zoology (Museum of Evolution - Uppsala). 608 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 255 records from Victorian Biodiversity Atlas. 23 records from Fish specimens of Natural History Museum, Kishiwada City. 939 records from Diversity of the Indo-Pacific (DIPnet). 115 records from Observations de poissons réalisées dans le cadre du programme PROCFish/C. 13 records from Données d'occurrence Espèces issues de la base Natura 2000 : espèces d'intérêt communautaire et autres espèces remarquables renseignées dans les FSD. 384 records from NESP A9: Grey Nurse Shark tissue sample collection, Australia (2002-2017). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences